Inovasi Komunikasi Pembangunan: Pemberdayaan Masyarakat di Desa Pinge melalui Edutourism - Putri Ekaresty Haes; Putu Ratna Juwita; Ni Putu Yunita Anggreswari; I Wayan Joniarta; Ayu Made Bianca Juarez (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
The research conducted in Pinge Village, Marga Tabanan Subdistrict, aims to explore edutourism activities carried out in the tourist village through community empowerment as a form of development communication innovation. This study presents findings obtained from qualitative research, employing data triangulation as a method to ensure data validity. Additionally, the researcher collected data through observations in the village over several days, interviews with informants, and documentation of relevant media. The results of this study reveal that edutourism is an appropriate tourism option to be implemented in the Pinge tourist village. Active community participation in edutourism strengthens social solidarity and enhances a sense of ownership towards local culture. Communication innovation in this context plays a crucial role in disseminating information about the village's potential, strengthening collaboration networks between the community and stakeholders, and increasing the visibility of Pinge Village as an educational tourism destination. Thus, edutourism not only contributes to the local economy but also ensures the sustainability of culture and the environment, making it a holistic and sustainable model for community empowerment. The edutourism programme in Pinge Village not only attracts tourists but also involves the community in the process of education and the preservation of local culture.